Pemanfaatan Photovoltaic System Hybrid On Grid Dengan Beban Mixer Untuk Mengurangi Energi Listrik Dari PLN - Purwohartono, Agus, Hasyim Asy'ari, ST., MT (2016)
Various studies and research conducted to process sunlight that has not been exploited to the maximum, especially in Indonesia, which is a tropical country and Indonesia is one country that passed the equator. At present the use of solar panels began to be developed as one of the alternative renewable energy sources, so this study to find ways to improve the efficiency of the use of solar panels of 120 Wp and use the inverter on the grid. This research was conducted in 2 hours 30 minutes, aims to determine the current and voltage of the solar panel so that researchers know the average power generated and capable of supplying performance mixer and efficient use of solar panels of 120 Wp and use the inverter on the grid to the mixer using a hybrid system expected mixer can be supplied from solar panels of 120 Wp and PLN (State Electricity Company) directly. The average power generated from the solar panels is 24.138181 W, observations made this lead to the conclusion that the use of solar panels with a hybrid system has not been able to supply the mixer with power of 140 W